2013
DOI: 10.4049/jimmunol.1203053
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Inhibitor Generates Stable Human Tolerogenic Dendritic Cells

Abstract: Tolerogenic dendritic cells (DCs) are a promising tool for a specific form of cellular therapy whereby immunological tolerance can be induced in the context of transplantation and autoimmunity. From libraries of bioactive lipids, nuclear receptor ligands, and kinase inhibitors, we screened conventional protein kinase C inhibitors (PKCIs) bisindolylmaleimide I, Gö6983, and Ro32-0432 with strong tolerogenic potential. PKCI-treated human DCs were generated by subjecting them to a maturation process after differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Induction of tolDC has been experimentally achieved by suppressive agents, including IL-10 and TGF-β; immunomodulatory drugs, such as dexamethasone and vitamin D; and genetic modification (14). Our previous study identified that a benzothiazole derivative, BD750 [2-(2-benzothiazoleyl)-4,5,6,7-tetrahydro-2H-indazol-3-ol, C 14 H 13 N 3 OS, MW: 271.3], is an inhibitor of JAK3/STAT5 signaling and can inhibit T cell proliferation (15).…”
Section: Introductionmentioning
confidence: 99%
“…Induction of tolDC has been experimentally achieved by suppressive agents, including IL-10 and TGF-β; immunomodulatory drugs, such as dexamethasone and vitamin D; and genetic modification (14). Our previous study identified that a benzothiazole derivative, BD750 [2-(2-benzothiazoleyl)-4,5,6,7-tetrahydro-2H-indazol-3-ol, C 14 H 13 N 3 OS, MW: 271.3], is an inhibitor of JAK3/STAT5 signaling and can inhibit T cell proliferation (15).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, disruption of signaling pathways linking microbial recognition receptors to NF-κB activation with small-molecule inhibitors of protein kinase C (PKC) or glycogen synthase kinase-3β (GSK-3β) up-regulates IL-10 production by lipopolysaccharide (LPS)-stimulated MΦs (17,18). Conversely, CREB activation by EP2/EP4 prostanoid receptor agonists like prostaglandin E 2 (PGE 2 ) promotes IL-10 production by myeloid cells (19).…”
mentioning
confidence: 99%
“…It must be taken into account that it is usually accepted that iDC, after antigen-"danger signal" become into mDC. However, recently it has been reported that after the stimulation with, some drugs, microorganisms, or the tumor microenvironment, iDC differentiation and/or mDC formation could be altered [25][26][27]. The analysis of tumor infiltrating DC in murine melanoma revealed the presence of myeloid and plasmacytoid DC populations, most of these DC appeared immature, but about a third expressed a mature phenotype [28].…”
Section: Discussionmentioning
confidence: 99%